HUBUNGAN GAYA HIDUP DENGAN PRESTASI AKADEMIK MAHASISWA KEPERAWATAN UNIVERSITAS RIAU - ', Khairunnisa '; Sabrian, Febriana '; ', Safri ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Student college more likely to have unhealthy life style, such as smoking, consuing unhealthy food and bad stress management. This study aims to find the corellation between lifestyle and the academic achievement of nursing students from University of Riau. The method used in this study isdescriptive corellation with cross sectional approach. The study was conducted at University of Riau Nursing Science Program. The number of sample were 146 students which were chosen using stratified random sampling technique. The analysis used Chi-Square test. The result of this study  find that nursing students who have healthy lifestyle are 53,42% and nursing students who have unhealthy lifestyle were 46,58%. Most of nursing students (71,23%) have excellent academic achievement. This result shows there is  no relation between lifestyle and the academic achievement of nursing students from University of Riau (p=0,371>0,05). This study recommends for nursing student to keep maintain healthy lifestyle and academic achievement. Keyword : Academic Achievement, Life Style.